(untitled) (Brazilian Geographical Journal, 2013)
The paper takes into account the Solidarity Purchasing Groups. In many European countries these groups of consumers are based on common interest not only in quality and healthy food, but also in the direct contact with producers. New relationships among consumers and farmers are established which appear to be complementary to the standard long retail circuits (Sonnino and Marsden, 2006). The study aims at illustrating and testing the hypothesis that the Solidatiry Purchasing Groups organize the food provision by through a polycentric decision system (Ostrom et al., 196; Ostrom, 2010). An empirical analysis is proposed which concerns with the organization of the decision-making processes in Solidarity Purchasing Groups (SPGs). Three typical case studies (Seawright, Gerring, 2008) were carried out in order to corroborate the hypothesis that polycentric governance systems are achieved by through constitutional processes (Grandori, 2010) aimed at achieving a horizontal distribution of critical decisions rights.